Pancreatic Cancer Disparities in African Americans. Issue 4 (May 2015) - Khawja, Shumaila N.; Mohammed, Somala; Silberfein, Eric J.; Musher, Benjamin L.; Fisher, William E.; Van Buren, George
<x xml:space="preserve">Abstract</x> Objectives Pancreatic cancer is the fourth leading cause of cancer-related deaths in the United States. The incidence of pancreatic cancer in African Americans is 50% to 90% higher than the incidence in other racial groups. African Americans also have the worst prognosis. This is an evidence-based review of pancreatic cancer in African Americans with particular emphasis on baseline characteristics, treatment, and survival. Methods We queried PubMed in search for articles describing racial disparities in pancreatic cancer. Two categories of terms were "anded" together: pancreatic cancer terms and race terms. The last search was performed on November 14, 2013. Results We summarized the data on pancreatic cancer baseline characteristics, treatment, and survival for African Americans that we obtained from the following databases: (1) Surveillance, Epidemiology, and End Results, 1988–2008; (2) California Cancer Registry 1988–1998; (3) Cancer Survivor Program of Orange County/San Diego Imperial Organization for Cancer Control, 1988–1998; and (4) Harris County, 1998–2010. Conclusions Overall, pancreatic cancer survival of African Americans has not significantly improved over the past several decades despite advances in multimodality therapy; African Americans continue to face worse outcomes than whites. Although baseline characteristics, treatment, and biological factors offer some explanation, they do not completely explain the disparities in incidence and survival.